Self-replication processes in nanosystems of informatics - Węgrzyn, Stefan; Winiarczyk, Ryszard; Znamirowski, Lech (Zielona Góra: Uniwersytet Zielonogórski)
Recent research on the nanotechnological processes of molecular products and object synthesis as well as research on the nanosystems of informatics, stimulates the development of technical systems of informatics. Until now, they have been used mainly for computational tasks when, similarly to biological organisms, they allowed the development of self-replicating products and complete objects.
Keywords: nanosystem of informatics; biological nanosystem of informatics; technical nanosystem of informatics; selfreplication